Glutamine Ameliorates Mucosal Damage Caused by Immune Responses to Duck Plague Virus - Yuanyuan Zhang; Lili Zhao; Yan Zhou; Chenxi Diao; Lingxia Han; Niu Yinjie; Shengwang Liu; Hongyan Chen (SAGE Publishing, 2017)
The immune-releasing effects of L-glutamine (Gln) supplementation in duck plague virus (DPV)-infected ducklings were evaluated in 120 seven-day-old ducklings that were divided into 8 groups. The ducklings in control and DPV, 0.5Gln and DPV + 0.5Gln, 1.0Gln and DPV + 1.0Gln, and 2.0Gln and DPV + 2.0Gln received 0, 0.5, 1.0, and 2.0 g of Gln/kg feed/d by gastric perfusion, respectively. Then, the ducklings in control to 2.0Gln were injected with 0.2 mL of phosphate-buffered saline, while those in DPV to DPV + 2.0Gln were injected with DPV at 0.2 mL of 2000 TCID 50 (50% tissue culture infection dose) 30 minutes after gavage with Gln, sampled at 12 hours and days 1, 2, 4, and 6. Glutamine supplementation under physiological conditions enhanced immune function and toll-like receptor 4 (TLR4) expressions in a dose-dependent manner. An increase in Gln supplementation under DPV-infected conditions enhanced growth performance, decreased immunoglobulin (Ig) release in plasma and secretory IgA in the duodenum, ameliorated plasma cytokine levels, and suppressed overexpressions of the TLR4 pathway in the duodenum. The positive effects of Gln on the humoral immunity- and intestinal inflammation-related damage should be considered a mechanism by which immunonutrition can assist in the recovery from DPV infection.